Amorphous Molecular Materials for Directed Supercontinuum Generation. Issue 12 (17th September 2021) - Dehnen, Stefanie; Schreiner, Peter R.; Chatterjee, Sangam; Volz, Kerstin; Rosemann, Nils W.; Pilgrim, Wolf‐Christian; Mollenhauer, Doreen; Sanna, Simone
Abstract: Molecular compounds of the general formula [(RT)4 E6 ] (R=organic or organometallic substituent; T=C, Si, Ge, Sn; E=CH2, S, Se), hence adamantane derivatives and inorganic‐organic hybrid compounds based on a heteroadamantane structure exhibit a non‐linear optical response upon radiation with a continuous‐wave near‐infrared laser. The effect depends on the compounds' habitus, which itself depends on the elemental composition of the cluster core, and on the nature of the organic substituents. A combination of these parameters that cause the material to be intrinsically amorphous leads to supercontinuum generation and thus to the emission of a broad spectrum, potentially appearing as white light. Notably, the emission essentially retains the driving laser's directionality. For crystalline samples, second harmonic generation is observed instead, which points to a close relationship of the optical properties and the intermolecular order. Variation of R, T, and E allows further fine‐tuning of the emitted spectra. We present all studies made in regards to these effects and our overarching conclusions derived from them. Abstract : White‐light generation : This Minireview summarizes current developments in the field of supercontinuum generation with amorphous molecular materials. The compounds in the focus of this work share a common general formula, [(RT)4 E6 ] (T=C, Si, Ge, Sn; E=CH2, S; Se, Te), in which a molecular organic or inorganic adamantane‐shaped cage is surrounded by four organic ligands R. All substances investigated in this context are described along with the results of experimental and theoretical analyses of their optical properties and the key parameters that influence the supercontinuum generation.